2020
DOI: 10.1140/epjc/s10052-020-7750-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase structures and transitions of Born–Infeld black holes in a grand canonical ensemble

Abstract: To make a Born-Infeld (BI) black hole thermally stable, we consider two types of boundary conditions, i.e., the asymptotically anti-de Sitter (AdS) space and a Dirichlet wall placed in the asymptotically flat space. The phase structures and transitions of these two types of BI black holes, namely BI-AdS black holes and BI black holes in a cavity, are investigated in a grand canonical ensemble, where the temperature and the potential are fixed. For BI-AdS black holes, the globally stable phases can be the therm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…And it was discovered that Gauss-Bonnet black holes in a cavity also have quite similar phase structure and transitions to the AdS counterparts [57]. However, it is shown that the phase structure of Born-Infeld black holes enclosed in a cavity has dissimilarities from that of Born-Infeld-AdS black holes [58,59]. Moreover, it is found that there exist significant differences between the thermodynamic geometry of RN black holes in a cavity and that of RN-AdS black holes [60], and some dissimilarities between the two cases also occur for validities of the second thermodynamic law and the weak cosmic censorship [61].…”
Section: Introductionmentioning
confidence: 99%
“…And it was discovered that Gauss-Bonnet black holes in a cavity also have quite similar phase structure and transitions to the AdS counterparts [57]. However, it is shown that the phase structure of Born-Infeld black holes enclosed in a cavity has dissimilarities from that of Born-Infeld-AdS black holes [58,59]. Moreover, it is found that there exist significant differences between the thermodynamic geometry of RN black holes in a cavity and that of RN-AdS black holes [60], and some dissimilarities between the two cases also occur for validities of the second thermodynamic law and the weak cosmic censorship [61].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was extended to the case of a RN black hole which was considered in a grand canonical ensemble [19] and a canonical ensemble [20,21]. The thermodynamic phases of diverse black holes in a cavity were discussed in [22][23][24][25][26][27][28][29][30][31], which indicated that the Van de Waals-like phase transitions or the Hawking-Page-like phase transitions exist invariably except for some particular cases. The relationship between thermodynamic properties of black holes and their specific boundary conditions in different extended phase spaces was studied in [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, we recently studied Born-Infeld black holes enclosed in a cavity in a canonical ensemble [56] and a grand canonical ensemble [57] and revealed that their phase structure has dissimilarities from that of Born-Infeld-AdS black holes. Moreover, contrary to the phase behavior, we found that there exist significant differences between the thermodynamic geometry of RN black holes in a cavity and that of RN-AdS black holes [58], and some dissimilarities between the two cases also occur for validities of the second thermodynamic law and the weak cosmic censorship [59].…”
Section: Introductionmentioning
confidence: 99%